THE ROLE OF ULTRASOUND IN THE EVALUATION OF APPENDICITIS FILES - Dr. Mazin Kauther Abdul Latif; Abduljabbar Jameel Asal; Kafia Raof Rashed (Scholar Express Journals, 2022)
This study aims to make a re-diagnosis of patients with appendic who underwent a diagnosis by other methods to know the problems the patients where Sixty patients were collected from different hospitals in Iraq, for the purpose of a reassessment of appendicitis patients A noticeable increase was observed in the positive predictive value of patients, as it exceeded 90%. As for the positive predictive value, it was sensitive to patients, where it was noted that a clear and present change in the diagnosis by ultrasound if compared to computerized tomography. Independent ultrasound findings to distinguish appendicitis were incompressible (p = 0.002) and increased flow on the appendix wall (p = 0.001). Appendicitis is an acute disease that requires immediate surgical intervention. Failure to take steps to remove the appendix from the body can lead to lifethreatening complications such as peritonitis. Inflammation can occur at any age.
Keywords: Appendicitis; ultrasound; UVA; preoperative